Law Enforcement Against Illegal Logging Activities in Sumalata District - Apriyanto Adam (Universitas Negeri Gorontalo, 2020)
Abstract:The purpose of writing in this study is to find out the effectiveness of Law Number 41 of 1999 concerning Forestry, Against Illegal Logging of Trees in Sumalata District. The writing of this article uses the Juridical Empirical research method, namely examining applicable legal provisions and observing what happens in social reality, by examining the population and samples and using primary and secondary data types, and using data collection techniques in the form of observation, interviews, and documentation. This article concludes that law enforcement against illegal logging of trees that occurred in Sumalata sub-district can be pursued by taking preventive measures, in the form of socialization or guidance to the community in the form of comprehensive patrol activities in friends prone to illegal logging, as well as with repressive actions to the perpetrators by imposing penalties by applicable laws. So that the realization of efforts to control and supervise illegal logging activities.Keywords: Effectiveness, Illegal Logging